(untitled) (Journal Of Educational and Psychological Researches, 2015)
That achieve a level of excellence for the quality of university education cannot be achieved only by uniting the efforts of all employees at the university and active participation by students and by alumni and the labor market and society, however we can say that the administrative and academic university staff play an active role and the largest in achieving equivalent quality of higher education, It should unite the efforts of all employees in the educational institution in order to achieve quality education. It is the concept of quality of education, quality assurance and overall management of the quality of the basic pillars on which it is based university education. That highlight the need for the application of the quality of education can not only be done through the construction of theoretical knowledge and monitoring the strengths and weaknesses of the education system and this leads to the full adoption and universal application of the concepts of total quality. The aim of research is to focus on quality assurance in sections teaching methods in colleges of education, was the study sample after the withdrawal of a random sample representative of the research community by (0.050) identify included five basic themes (quality assurance input, management practices, quality assurance system , the quality of operations, the quality of output) on the sample, and analyzed using appropriate statistical media for the research community, including the arithmetic mean and T test .of the search to a set of recommendations and proposals